Primer registro de Eupteryx decemnotata (Cicadellidae: Typhlocybinae) en la Argentina - De Borbon, Carlos Manuel (2022)
Eupteryx decemnotata (Rey) is an oligophagous species of potential economic importance. It is native to Mediterranean region. Then, it spread throughout most of Europe and reached North America. In this work it is recorded for the first time in Argentina. Distinctive characters of the species are mentioned and illustrated.